Pengaruh Promosi, Branding Dan Kepuasan Pelanggan Terhadap Loyalitas Konsumen Kopi Janji Jiwa Di Karawang Galuhmas - Putri, Indah Greszesky; Zed, Etty Zuliawati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The surge in coffee demand every year attracts many entrepreneurs and aspiring business owners to enter the coffee beverage market. The coffee industry in Galuhmas Karawang is experiencing growth. The purpose of this study was to determine the effect of promotional variables, branding, and customer satisfaction on consumer loyalty. In conducting this research using SPSS software. The research analysis method uses validity, reliability, normality test, correlation test, multiple linear regression analysis test, and hypothesis testing. The results of this study are that the promotion variable has a positive and insignificant effect on consumer loyalty, the branding variable has a positive and significant effect on consumer loyalty, and the customer satisfaction variable has a positive and insignificant effect on consumer loyalty.